Children with Autism Show Altered Autonomic Adaptation to Novel and Familiar Social Partners. Issue 5 (25th August 2015) - Neuhaus, Emily; Bernier, Raphael A.; Beauchaine, Theodore P.
Abstract : Social deficits are fundamental to autism spectrum disorder (ASD), and a growing body of research implicates altered functioning of the autonomic nervous system (ANS), including both sympathetic and parasympathetic branches. However, few studies have explored both branches concurrently in ASD, particularly within the context of social interaction. The current study investigates patterns of change in indices of sympathetic (pre‐ejection period; PEP) and parasympathetic (respiratory sinus arrhythmia; RSA) cardiac influence as boys (ages 8–11 years) with ( N = 18) and without ( N = 18) ASD engage in dyadic social interaction with novel and familiar social partners. Groups showed similar patterns of autonomic change during interaction with the novel partner, but differed in heart rate, PEP, and RSA reactivity while interacting with a familiar partner. Boys without ASD evinced decreasing sympathetic and increasing parasympathetic influence, whereas boys with ASD increased in sympathetic influence. Boys without ASD also demonstrated more consistent ANS responses across partners than those with ASD, with parasympathetic responding differentiating familiar and novel interaction partners. Finally, PEP slopes with a familiar partner correlated with boys' social skills. Implications include the importance of considering autonomic state during clinical assessment and treatment, and the potential value of regulation strategies as a complement to intervention programs aiming to support social cognition and behavior. Autism Res 2016, 9: 579–591 . © 2015 International Society for Autism Research, Wiley Periodicals, Inc.